2016
DOI: 10.1080/09168451.2016.1164587
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of sword bean proteins by heating and addition of magnesium chloride in a crude extract

Abstract: Sword bean (Canavalia gladiata) seeds are a traditional food in Asian countries. In this study, we aimed to determine the optimal methods for the precipitation of sword bean proteins useful for the food development. The soaking time for sword beans was determined by comparing it with that for soybeans. Sword bean proteins were extracted from dried seeds in distilled water using novel methods. We found that most proteins could be precipitated by heating the extract at more than 90 °C. Interestingly, adding magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…In our previous study, we described a method for the extraction of proteins from sword bean in distilled water and their precipitation by the addition of 20 mM MgCl 2 in the crude extract. 5) This was the first study that reported the precipitation of canavalin in the presence of MgCl 2 and showed that a detailed investigation of canavalin precipitation might be important for the study of its physiological function and physicochemical properties.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…In our previous study, we described a method for the extraction of proteins from sword bean in distilled water and their precipitation by the addition of 20 mM MgCl 2 in the crude extract. 5) This was the first study that reported the precipitation of canavalin in the presence of MgCl 2 and showed that a detailed investigation of canavalin precipitation might be important for the study of its physiological function and physicochemical properties.…”
mentioning
confidence: 97%
“…We have previously reported a method for the extraction of some proteins from sword bean using only distilled water. 5) In addition, the predominant protein in the crude extract was determined to be canavalin. 5) Canavalin is the major storage protein of sword bean and jack bean (Canavalia ensiformis) with a molecular mass of 47.6 kDa, classified as 7S seed globulin or legume vicilin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The agricultural and nutritional characteristics show the potential for utilizing sword beans in processed foods. Previously, we reported the physicochemical characteristics of sword bean proteins [5,6] and gelation of sword bean extract [7], both of which are important for making processed foods. However, more scientific knowledge is essential to begin using sword beans to make processed foods.…”
mentioning
confidence: 99%
“…In our previous studies, dried WSBs were used for protein extraction after water absorption by soaking [5,6]. Dried WSBs absorbed sufficient water for extraction purposes after soaking in 10 volumes of distilled water for 18 h at 20°C [5]. However, dried RSBs absorbed a little amount of distilled water, in contrast to dried WSBs.…”
mentioning
confidence: 99%